Formulation of a 7, 2′, 4′-trihydroxyflavanone oil-in-water microemulsion using aqua coconut oil: Characterization, stability, and antibrowning effects on fresh apple juice. (July 2018) - Tao, Jing; Zheng, Zong-Ping; Guo, Fengxian; Chen, Jie
Abstract: In this study, a food grade water in oil (O/W) microemulsion to improve the solubility and stability of 7, 2′, 4′-trihydroxyflavanone was developed, and its ability to inhibit on the browning of fresh apple juice was also investigated. The results showed that the solubility of 7, 2′, 4′-trihydroxyflavanone in the aqua coconut oil microemulsion was up to 22.380 ± 0.336 mg/mL, which is approximately a 2000-fold solubility increase compared with that in water (0.011 mg/mL). The results of acceleration and long-term testing indicated thats the selected microemulsions were stable. The addition of VC into the 7, 2′, 4′-trihydroxyflavanone microemulsion (TME) greatly improved the solubility and stability of 7, 2′, 4′-trihydroxyflavanone. A 0.01% final concentration of TME performed well at inhibiting the browning of fresh apple juice during storage for 24 h at room temperature and for 7 days at 4 °C, and the antibrowning effect was further improved when a 0.05% VC concentration was added in combination with the TME. These results demonstrated that 7, 2′, 4′-trihydroxyflavanone microemulsion holds potential as a new antibrowning agent for fresh apple juice. Highlights: Aqua coconut oil was used as the oil phase to form the MEs. Various MEs including four TME were developed and characterized. MEs greatly improved 7, 2′, 4′-trihydroxyflavanone solubility in water system. Various MEs were found to be stable after acceleration and long-term storage. TME and T+VC ME showed strong inhibition effects on fresh apple juice browning.